2022
DOI: 10.3390/jcm11133674
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of DNA Damage Response via the Ccndbp1–Atm–Chk2 Pathway in Mice with Dextran-Sodium-Sulfate-Induced Colitis

Abstract: The dextran sodium sulfate (DSS)-induced colitis mouse model has been widely utilized for human colitis research. While its mechanism involves a response to double-strand deoxyribonucleic acid (DNA) damage, ataxia telangiectasia mutated (Atm)–checkpoint kinase 2 (Chk2) pathway activation related to such response remains unreported. Recently, we reported that cyclin D1-binding protein 1 (Ccndbp1) activates the pathway reflecting DNA damage in its knockout mice. Thus, this study aimed to examine the contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These results suggested that Ccndbp1 contributed to activating the Atm–Chk2 pathway, in turn triggering inflammation and apoptosis of mucosal cells in the colon. (“Involvement of DNA Damage Response via the Ccndbp1-Atm-Chk2 Pathway in Mice with Dextran-Sodium-Sulfate-Induced Colitis” by Horirome et al [ 6 ]). Based on this progress, it is essential to evaluate CCNDBP1 expression in the human liver samples of various chronic liver diseases that cause inflammation and fibrotic changes, and ultimately to apply these results to novel molecular therapy for the liver tumor.…”
mentioning
confidence: 99%
“…These results suggested that Ccndbp1 contributed to activating the Atm–Chk2 pathway, in turn triggering inflammation and apoptosis of mucosal cells in the colon. (“Involvement of DNA Damage Response via the Ccndbp1-Atm-Chk2 Pathway in Mice with Dextran-Sodium-Sulfate-Induced Colitis” by Horirome et al [ 6 ]). Based on this progress, it is essential to evaluate CCNDBP1 expression in the human liver samples of various chronic liver diseases that cause inflammation and fibrotic changes, and ultimately to apply these results to novel molecular therapy for the liver tumor.…”
mentioning
confidence: 99%